Avatar 'n' Andy: The Colour Blind Ideology in Video Game Voice Acting - Miletic, Philip (Loading, 2020)
Despite recent criticisms that call out blackface in video game voice acting, the term “blackface” was and still is seldomly used to describe the act of casting white voice actors as characters of colour. As a result, the act of blackface in video game voice acting still occurs because of colorblind claims surrounding the digital medium and culture of games. In this paper, I position blackface in video game voice acting within a technological and cultural history of oral blackface and white sonic norms. I focus on three time periods: the Intellivision Intellivoice and the invention of a "universal" voice in video games; early American radio in the 1920s-1930s and the national standardization of voice; and colorblind rhetoric of contemporary game publishers/devs and voice actors.